2020
DOI: 10.1109/tmi.2019.2922026
|View full text |Cite
|
Sign up to set email alerts
|

A Partially-Learned Algorithm for Joint Photo-acoustic Reconstruction and Segmentation

Abstract: In an inhomogeneously illuminated photoacoustic image, important information like vascular geometry is not readily available when only the initial pressure is reconstructed. To obtain the desired information, algorithms for image segmentation are often applied as a post-processing step. In this work, we propose to jointly acquire the photoacoustic reconstruction and segmentation, by modifying a recently developed partially learned algorithm based on a convolutional neural network. We investigate the stability … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 60 publications
0
45
0
Order By: Relevance
“…Finally, we will explore the possibility to perform photoacoustic reconstruction and segmentation simultaneously using a partially learned algorithm. 20 As a basis for this future work, the robustness analysis performed here demonstrates that it is important to have enough variety in image intensities in the training set.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, we will explore the possibility to perform photoacoustic reconstruction and segmentation simultaneously using a partially learned algorithm. 20 As a basis for this future work, the robustness analysis performed here demonstrates that it is important to have enough variety in image intensities in the training set.…”
Section: Discussionmentioning
confidence: 95%
“…For reconstructions in PAT, the work by Boink et al [137][138][139] has demonstrated the robustness of these learned iterative schemes to a number of in silico phantoms as well as in an experimental study. The authors consider an extension to the learned gradient schemes introduced above called learned primal dual 18 (LPD) based on the successful primal-dual hybrid gradient method 140 (also known as the Chambolle-Pock algorithm).…”
Section: Learned Primal Dual In 2dmentioning
confidence: 99%
“…5(b). In their work, [137][138][139] the authors examined the robustness of LPD with respect to changes in the target, including the contrast, background, structural changes, and noise level. They found that if the network is trained only on the basic training data, it generalizes fairly well with respect to noise (1 dB degradation in PSNR) and structural changes (3 dB), but is most sensitive to changes in background (7 dB) and contrast (11 dB).…”
Section: Learned Primal Dual In 2dmentioning
confidence: 99%
See 1 more Smart Citation
“…They designed a DNN to represent the iteration framework and introduced the gradient information of the photoacoustic data (Figure 7B). Boink et al designed a CNN network based on partially learned algorithm to simultaneously achieve image reconstruction and segmentation of PAT (96). Compared with the strategy of using U-Net for post-processing network, the reconstruction results are further improved by the iterative network.…”
Section: Patmentioning
confidence: 99%